PENERAPAN MULTIMEDIA UNTUK MENINGKATKAN MOTIVASI DALAM PEMBELAJARAN IPA SISWA KELAS 4 SDIT CORDOVA SAMARINDA - Desi Hermawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
The purpose of the research is to improve students' motivation of SDIT Cordova Samarinda through learning implementation of multimedia. This research is a Classroom Action Research which conducted in the fourth grade elementary school of SDIT Cordova Samarinda’s students as the subject. This action research conducted in three cycles which executed on March until April 2009. The data was collected through observations, interviews, and final scores. Data analysis carried out to obtain data (1) The learning implementation of multimedia method, (2) Students response toward multimedia method, (3) Students achievement results during multimedia method. Data analyzing with qualitative data analysis model by Miles and Huberman. The steps of data analysis are data reduction, data display and conclusion drawing/ verification. The results of this research show the application of multimedia method can improve the learning process and student motivation in Science. Furthermore there is a significant improvement of students motivation. However, there are some student who can’t manage their note. so that we suggest teachers should combine the various methods and techniques including quotation to maximize the learning process and learning outcomes.Keywords: multimedia, motivation, learning process